Analysis of Al-Qur'an Learning The Ummi Metode Method at Islamic Elementary School: Analisis Pembelajaran Al-Qur’an Metode Ummi di Sekolah Dasar Islam - A'yun, Tsamara Qurrota; Romadlon, Dzulfikar Akbar (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to analyze the ummi method of learning the Qur'an at SD Islam Sari Bumi Sidoarjo. The research method used is descriptive qualitative which produces data in the form of written words from the results of interviews, observations and documentation. Thel results showedl that thel coordinator's stepsl in learningl the Qur'anl using the ummil method were guided by the rules set by the Ummi Foundation. In its implementation, the ummil method refersl to thel learning stagesl that havel been determined by the Ummil Foundation andl adds al slight variationl to the implementation process. The results of the Ummi method learning process have a very good impact on students' ability to read the Qur'an and the implementation procedures for the supervision of the Ummi method through internal training for strengthening tadarus, class management and perfect prayer training. This can be seen from the report during January-March 2022 which has a good outcome in improving students' ability to read the Qur'an. Because after the Ummi method learning process is carried out, students' readings become good, correct and according to the standards set by the Ummi Foundation.